The electric field jump—detection of damaged Nb barrier in MgB2 wires annealed under pressure. (15th September 2015) - Gajda, D; Zaleski, A J; Morawski, A; Rindfleisch, M; Thong, C; Tomsic, M
Abstract: In this paper we present the results of critical current ( I c ) measurements of MgB2 wires made with two different set-ups of the four-point probe method: current sweep type—constant magnetic field and increasing current, and field sweep type—constant current and rapidly increasing magnetic field. Results from magnet field sweep type measurements can be interpreted by a new physical concept—a jump of the electric field in low magnetic fields. This physical concept can be correlated with damages in the Nb-barrier existing in the MgB2 wire and be employed as a detection scheme. The damage in Nb barrier reduces critical current density ( J c ) and complicates the study on critical temperature ( T c ), upper critical field ( B c2 ), irreversible magnetic field ( B irr ), pinning force ( F p ), and pinning centers in superconducting MgB2 wires. Our proposed method to detect damages in Nb barrier would benefit efforts in development and applications of MgB2 wires.